Terapia manual ortopédica aplicada a pacientes con trastornos temporomandibulares. - Coronel Valencia, Adrian Alejandro (2024)
Temporomandibular disorders, a significant health concern recognized by the World Health Organization, rank as the third most common cause of oral diseases. Bruxism events, malocclusions, occlusal interferences, tooth loss, and direct or indirect trauma in the temporomandibular joint can trigger these disorders. Currently, there is a high prevalence of these disorders in the female population, with a ratio of 3 to 1 compared to the male population. Considering this, the study proposes orthopedic manual therapy as a promising solution for treating patients with temporomandibular disorders, offering hope for improved patient outcomes. A comprehensive search was meticulously carried out in different scientific databases such as Scopus, PubMed, and PEDro. From a population of 237 randomized clinical trials, 25 were selected that met all the inclusion criteria, including having been published in the last six years and achieving a score equal to or greater than six on the PEDro scale, ensuring the reliability of the study's findings. The results of the study revealed a strong preference for manual therapy. When combined with other physiotherapy techniques, particularly exercise, it proves to be more effective in addressing functional limitations, increasing strength and joint range, and improving pain. The adoption of a multidisciplinary approach, which includes dentistry for oral health, psychology for mental well-being, and traumatology for injury management, holds the promise of significantly reducing patient recovery times. Most clinical trials unequivocally demonstrated the effectiveness of manual therapy as a treatment for temporomandibular disorders in patients with this condition. Manual therapy effectively alleviates the symptoms associated with pain, such as joint and muscle dysfunction, which affects the range of opening and, therefore, the quality of life and patient participation, providing reassurance about its potential to improve patient outcomes.